Analisis Kemampuan Menulis Naskah Drama pada Siswa Kelas VIII di SMP Negeri 1 Mandau - Febiola, Ranti; Tinambunan, Jamilin (UIR Press, 2024)
This study investigates students' ability in writing drama scripts at SMP Negeri 1 Mandau, Bengkalis Regency, in the academic year 2022/2023. The main objective is to obtain information about students' ability in writing drama scripts, an activity that requires a high level of creativity to produce stimulating works. This skill not only aids in the development of students' personalities and creativity but also enables them to express their ideas, thoughts, and imagination through written media. The study addresses the primary issue of the extent of students' ability in writing drama scripts at SMP Negeri 1 Mandau, Bengkalis Regency, in the academic year 2022/2023. By using a quantitative approach and descriptive method, the research findings indicate that the ability of eighth-grade students in writing drama scripts is categorized as quite good, with a range of scores between 60 to 70. Observation and test techniques are employed in data collection, and based on the analysis of the elements of writing drama scripts, the average score of students is 60.86, also categorized as quite good.